On Joachimsthal's theorems in Riemann Otsuki space R ? O3 - Yılmaz, Münevver Yıldırım; Bektaş, Mehmet (My University, 2014)
In this paper we study the Joachimsthal theorem in Riemann Otsuki space
Keywords: Fizik; Matematik